2019
DOI: 10.1155/2019/9241928
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endoscopic Management of a Renal Fungal Ball using Flexible Ureterorenoscopy

Abstract: Background. Candida as a cause for urinary tract infection in healthy individuals is unusual. The extension of fungi into the urinary collecting system rarely leads to formation of bezoars or fungus balls. This can in turn lead to hydronephrosis, obstructive uropathy and sepsis. Case Presentation. An eighty years old gentleman presented to A&E with confusion, severe urosepsis and acute kidney injury. CTKUB demonstrated significant right sided hydronephrosis, perinephric fat stranding and gas in collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 3 , 5 , 9 Fungal balls could be also directly extracted using flexible ureteroscopy, cystoscopy, PCNL, or by surgical exploration in more complicated cases. 10 - 14 ,21,22 In our case, the treatment of the fungal balls with a systemic antifungal agent (fluconazole) was sufficient enough for a complete eradication of an extensive fungal bezoar infection that was extending through the calyceal systems, ureters, and urinary bladder.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“… 3 , 5 , 9 Fungal balls could be also directly extracted using flexible ureteroscopy, cystoscopy, PCNL, or by surgical exploration in more complicated cases. 10 - 14 ,21,22 In our case, the treatment of the fungal balls with a systemic antifungal agent (fluconazole) was sufficient enough for a complete eradication of an extensive fungal bezoar infection that was extending through the calyceal systems, ureters, and urinary bladder.…”
Section: Discussionmentioning
confidence: 67%
“…Renal pelvis and ureteric bezoars might cause an obstruction with hydronephrosis and elevated kidney function test in which case a nephrostomy or a ureteric stent is usually necessary. [9][10][11][12] The bladder outlet may also get obstructed by the fluffy material of the bezoars and in rare cases, it may lead to bladder perforation if not promptly managed by catheterization. 13,14 As in this case, fungal urinary tract infections may spread through the urinary tract to cause an extensive infection through the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…As Abuelnaga et al also demonstrated, endoscopic retrieval of the renal tissues by ureteroscopy can be an effective and rapid way to manage fungal balls. The hospital stay and toxicity associated with antifungals can hereby be reduced, in comparison to installation through nephrostomy [5]. Especially in cases where a diagnostic URS is carried out or in cases where a nephrostomy is contraindicated, the URS should be considered as a first line treatment, in combination with systemic antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that involvement of ophthalmology in cases of fungemia due to urinary tract fungal ball is critical, even with no ocular symptoms present. In lieu of typical first-line antifungals such as fluconazole, urinary tract fungal balls require special multidisciplinary management like nephrostomy tubes, antifungal irrigation, ureterorenoscopy, and more powerful antifungals such as amphotericin B and 5-flucytosine [ 5 , 13 15 ]. Although chronic echinocandins are not thought of as good drugs for the urinary tract, there are case series and case reports of successful treatment of Candida species with micafungin while subsequently avoiding the toxicity of the previously mentioned antifungals such as amphotericin B [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%